행정표준코드의 기관코드를 활용한 공공데이터의 품질 개선 방법 제안 - 김현지(Hyeonji Kim); 김학래(Haklae Kim) (디지털콘텐츠학회논문지, 2022)
데이터 품질은 데이터 생애주기 전 과정에서 고려해야 하는 중요한 원칙이다. 정부는 공공데이터 품질을 확보하기 위해 공공기관의 품질관리 수준을 평가하고, 품질평가 지표를 제시하고 있다. 그러나 기존 품질관리 평가는 기관 데이터베이스를 중심으로 구성되어 있어 데이터값 수준의 평가에 적용하기 어렵다. 개방된 데이터세트에 대한 품질평가는 메타데이터나 일부 항목의 값 형식을 평가한다. 데이터값 수준의 정확성을 평가하고, 오류값을 정확한 값으로 개선하는 연구는 부족하다. 본 논문은 공공데이터포털에 개방된 데이터세트를 대상으로 값 수준의 품질을 평가하고, 행정표준코드 중 기관코드를 적용해 기관명 데이터의 품질을 개선하는 방법을 제안한다. 행정표준코드는 행정기관의 데이터베이스에서 사용하는 표준코드로, 기관과 관련된 기관코드를 포함한다. 품질평가 지표는 값 수준의 품질을 평가할 수 있는 완전성과 정확성을 사용한다. 평가 결과, 공공데이터포털에 개방된 파일데이터의 완전성은 0.74이며, 부정확한 기관명 데이터 859,509건의 값을 개선했다. Data quality is an important requisite to be considered throughout the data lifecycle. In order to secure the quality of public data, Korea government evaluates the data quality management level of administrative institutions and presents data quality indicators. However, the existing quality management process is organized around the database, making it difficult to apply to the dataset. Quality evaluation for opened datasets usually targets the format of values of specific attributes or metadata. There are insufficient studies to evaluate the quality of data value and improve the error value to the correct value. This paper evaluates the quality of public data released to public data portal and proposes a method to improve the quality of data by applying administrative standard codes. Quality evaluation indicators use completeness and accuracy to evaluate the quality of the value. As a result of the evaluation, the completeness of the file data released to the public data portal is 0.74, and 859,509 rows of inaccurate organization name is improved. KCI Citation Count: 1